Analisis Daya Saing Biji Kopi Indonesia di Pasar Internasional - Zacharie, Raja; Denny, Saputera (SAFE-Network, 2024)
This study aims to analyze the competitive advantage of Indonesian coffee beans in the international market. By using export data from 2015-2022. This research examines the factors influencing Indonesia’s coffee exports and compares Indonesia’s position with major coffee producers. The results highlight Indonesia significant role in the global coffee market and identify key areas for enchancing its competitive advantage. The Revealed Comparative Advantage (RCA) value of Indonesian coffee shows fluctuations during the 2015-2022 period, with an average value of 3.11. This value is the lowest compared to the main competing countries. A significant decline in the RCA value occurred in 2017 and 2018, which indicates that the competitiveness of Indonesian coffee in the international market has decreased in those years. Apart from that, Indonesia has several competitive advantages, especially in terms of quality and diversification of coffee varieties. However, this advantage has not been fully utilized to increase export competitiveness. Government support and innovation in the coffee industry are also important factors influencing competitiveness. Incentive programs and infrastructure improvements need to be increased to support the growth of this sector. The condition of Indonesian coffee exports shows that even though Indonesia is one of the largest coffee producing countries in the world, its position in the export market is still inferior compared to developed countries. Implementation of new technology, farmer training, investment in processing infrastructure, and quality certification can help increase the competitiveness of Indonesian coffee. Close collaboration between the government, private sector and farmers is essential to achieve this goal and strengthen Indonesia's position as a leading coffee producer in the world.